Doctrine of corporate governance and competition laws: The Malaysian perspectives - Choong, K.F.; Wong, E.S.K.; Yap, P. (Academic Journals, 2010)
This study examines the issues of competition law in Malaysia. These issues had challenges not only in its goal towards a market economy, but also in its national re-engineering of the economy under Malaysia’s industrialization plan. Malaysia has reached now reached that goal. The main issues were the impediments as to whether or not to introduce a structured, broader competition law in Malaysia. Often, in Malaysia, when markets were unable or unwilling to provide goods, services, or competition, the State became involved in the establishing of a free market. Malaysia has done this in its Capital Market Master plan, and the pressing challenges were on local trade issues. The trade barrier issues in Malaysia were different, as unique issues concerned culturally and historically based protection zones. Documents from several Articles (81 and 82) of the European Community Treaty, a variety of United States statutes such as The Sherman Antitrust Act, The Clayton Antitrust Act, The Federal Trade Commission Act and The Antitrust Criminal Penalty Enhancement and Reform Act of 2004, and also Malaysian government guidelines were scrutinized in studying and establishing The Doctrine of Malaysia’s Competition aw, with its various attributes in illustrating corporate governance. The citation of three case studies to illustrate how competition legislation worked in the EU, UK, US and Malaysia provided the foundation of the new laws dealing with competitive practices. Malaysia needed to determine its primary of focus that is the producers and suppliers or the consumers. The US model protected the producers whilst the EU model shielded the consumers. The US model was more interested in economic and econometric results while the EU model emphasized social and regional development and the political consequences as well. The EU also protect the rights of small businesses more vigorously than the American legislation and, the EU to some extent, sacrifices intellectual property rights in the name of fairness and the free movement of goods and services. In the case of Malaysia, it seemed that Malaysia was more inclined to the EU than the American models. The purpose of this study is to illustrate competition laws deemed to secure a competitive marketplace and thus protect the consumers from unfair, anti-competitive practices. Yet, competition laws had to embody the inherent conflicts in emerging markets such as those in Malaysia, as well as a system of conflict resolution.